Ovarian degeneration resulting in the phenotypic masculinisation of a wild female Mallard Anas platyrhynchos - Lavretsky, Philip; Hernandez, Flor; Davis, Brian (Wildfowl, 2022)
Among dichromatic avian species, the loss of sexual organs can induce reversal of sexual features among females and males. In particular, the phenotypic feminisation or masculinisation of males and females, respectively, has been linked to the presence of testosterone or luteinizing hormones. Specifically, females lacking a functional ovary (e.g. experience an ovariectomy) or males lacking testes have been found to exhibit male breeding plumage in subsequent moult cycles. We conducted post mortem examination on a wild Mallard Anas platyrhynchos, determined genetically as a female but displaying male plumage, and found that the ovary was missing despite the remaining sexual organs being intact. We concluded that this individual provided an example of spontaneous ovarian degeneration, and that its male-like plumage was attributable to a resulting lack of oestrogen in its body. Together, these results further establish that plumage expression is not strictly genetically based, but rather dictated by the ability for the timely expression or suppression of these genes via modifiers, begging the question of why both sexes retain the molecular variation required to express the male plumage.